Isolation of plasma membrane domains from murine T lymphocytes. - Hoessli, D C (1983)
Murine T-lymphoma cells have been homogenized in dense sucrose solution and centrifuged under isopycnic conditions for membrane components. Floating fractions banding between 10% and 22.5% sucrose ("light" membranes) and between 22.5% and 35% sucrose ("heavy" membranes) were shown to consist of smooth membrane vesicles. The amounts of cholesterol and phospholipids recovered after chloroform/methanol extraction were similar in both fractions, but heavy membranes contained two to three times more protein than light membranes. The most striking difference between the two membrane fractions was revealed by their labeled surface glycoprotein patterns on polyacrylamide gels, suggesting that (i) the smooth membrane vesicles originated from the plasma membrane and (ii) two distinct segments of the plasma membrane can be recovered in fractions characterized by specific surface glycoproteins. Light membranes were enriched in Thy-1 antigen, whereas Ly-5 antigen and a 170,000-dalton surface glycoprotein were recovered almost exclusively from heavy membranes, as were metabolically labeled protein spots comigrating with the H-2k/d antigen in two-dimensional electrophoresis. The patterns of the unlabeled proteins in light and heavy membranes appeared similar, except for polypeptides of 180,000 and 85,000 daltons that were found preferentially in heavy membranes. These results support the concept of plasma membrane domains by showing that two distinct populations of plasma membrane vesicles can be isolated and that these populations contain different sets of cell surface glycoproteins.